The pharmacy as a primary care provider - Mor, Nachiket; Sen, Dyuti; Zaheen, Sarah; Khan, Rubayat; Naik, Priya; Basu, Nayonika (Frontiers in Public Health, 2023)
Primary care is an essential component of any health system, but building highquality primary care has proven to be a challenge for most developing countries. Among the multiplicity of providers in South Asia, one of the most ubiquitous channels through which not only are medicines obtained, but primary care advice is also sought, are the neighbourhood pharmacies. There is widespread availability of pharmacies in South Asia. There is also good evidence that working with pharmacies in this way is a globally accepted idea, and there are several examples of countries, such as France and Nigeria, that have integrated pharmacies into their primary care systems and have entrusted them with significant responsibilities. In this paper, we explore the potential of this channel as a formal primary care provider, with a particular focus on the South Asian context, by examining how pharmacies perform against the seven Starfield attributes of (i) first contact care, (ii) continuity of care, (iii) comprehensiveness, (iv) coordination, (v) family centredness, (vi) cultural competency, and (vii) community orientation. In the paper, we use data on pharmacies from four pharmacy-related interventions, one from Bangladesh and three from India, to carry out our analysis using the Qualitative Comparative Analysis (QCA) framework. We find that even in the South Asian context, pharmacies provide several components of good primary care. As expected, they demonstrate a strong orientation toward the community in which they are located and are able to provide first-contact care. However, we find no direct evidence that they are able to offer continuity of care or bring to bear family-centredness and cultural competency when dealing with their patients. It is encouraging, however, that while there is no formal evidence of this in any of the interventions, multiple anecdotal examples suggest that pharmacists do indeed do much of this, but perhaps in an informal and inconsistent manner. The evidence from these studies provides support for the view that pharmacies have many of the inherent characteristics needed to become an effective primary care channel and already play an important role in providing access to health information and care.